ANALISA PENETAPAN PRIORITAS PEMBANGUNAN DALAM MUSRENBANG DESA BOKOR KECAMATAN RANGSANG BARAT KABUPATEN KEPULAUAN MERANTI TAHUN 2020-2021 - Ricky Syuldairi; Adlin ' (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Villages have the authority to manage Village Funds which are given directly by the Central Government in the State Revenue and Expenditure Budget (APBN). The problem in this research is that in the Bokor Village Musrenbang for potential development in the economic sector it was not proposed by the community who proposed more to the infrastructure sector and other fields, the determination of development priorities was determined by the Bokor Village Government and Bokor BPD which were not in accordance with the PDTT Village Minister Regulation RI. The purpose of this study is to understand the setting of development priorities in the Musrenbang Bokor Village, Rangsang Barat District, Meranti Islands Regency for 2020-2021. This study uses the theory of priority principles for the use of Village Funds from the Regulation of the Minister of Villages, Development of Disadvantaged Regions, and Transmigration concerning Priority Use of Village Funds for 2020 and 2021 which consist of: principles of humanity, principles of justice, principles of diversity, principles of natural balance and principles of national interest. The approach used in this study is a qualitative approach. This type of research is descriptive. The location of this research is in Meranti Islands Regency, precisely in the West Rangsang Sub-District Office, the Bokor Village Head Office and the Bokor Mandiri Village Owned Enterprise (BUMDes) Office. The types of data in this study are divided into primary data using data collection techniques through interviews and secondary data in the form of supporting data related to the priority activity plans for the development of Bokor Village. The data collection techniques through interviews and documentation. The data analysis technique used is a qualitative analysis technique. Research results from setting development priorities in the Bokor Village Musrenbang for 2020-2021 are not going well, this is because there are several causes that are not fulfilled, namely community participation which leads to infrastructure development and not towards economic development, as well as the budget received by Bokor Village insufficient for economic development. Keywords: Development Priority, Musrenbang, Bokor Village